If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.5(3x + -6) = 3(x + -2) Reorder the terms: 1.5(-6 + 3x) = 3(x + -2) (-6 * 1.5 + 3x * 1.5) = 3(x + -2) (-9 + 4.5x) = 3(x + -2) Reorder the terms: -9 + 4.5x = 3(-2 + x) -9 + 4.5x = (-2 * 3 + x * 3) -9 + 4.5x = (-6 + 3x) Solving -9 + 4.5x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + 4.5x + -3x = -6 + 3x + -3x Combine like terms: 4.5x + -3x = 1.5x -9 + 1.5x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 1.5x = -6 + 0 -9 + 1.5x = -6 Add '9' to each side of the equation. -9 + 9 + 1.5x = -6 + 9 Combine like terms: -9 + 9 = 0 0 + 1.5x = -6 + 9 1.5x = -6 + 9 Combine like terms: -6 + 9 = 3 1.5x = 3 Divide each side by '1.5'. x = 2 Simplifying x = 2
| -x+29=13+2x | | 2x-4+6=36 | | 3n+46=1+38n | | 4(x-5)-3(x+1)-14=-28 | | -20=20-5v | | av-6=k | | x+(x*.0725)=7.45 | | 8y+5y+8= | | 2[4z-1]=3[z+h] | | 62-x=2x+3 | | (12)(b)(13)=338 | | 12xy-16x= | | 3x-24=-72 | | 12y-7=13+2y | | 100y^2+72y-4=0 | | xy+v=3 | | 12y-7=13+2 | | -3(n-3)-(3n-5)=-5+(3n-4) | | 5cosx=2.5 | | 2n=400 | | 4y-3(5c-2x+2)= | | 12y=-132 | | 6x+10+4x+15+20=180 | | 49=y+2x | | 2x^5-5x^4+10x^3-4x^2=0 | | 39-12w=7-162 | | (4-3i)(2-2i)=0 | | 2x^2-20x=28 | | y=-11x+3 | | 4m^2+20m-56=0 | | x+39=5x+3 | | 8x(x-4)=10x^2-33x |